A new synanthropic species of Charinus Simon, 1892 from Brazilian Amazonia and notes on the genus (Arachnida: Amblypygi: Charinidae) - de Miranda, Gustavo Silva; de Leão Giupponi, Alessandro Ponce (Zootaxa, 2011)
A new species of the genus Charinus—C. vulgaris— is described from Porto Velho, Rondônia. This is the first record of the family Charinidae from the Brazilian Amazonia and of a synanthropic species in South America. Additionally, two new records of the genus for Brazil are made and a key to the Brazilian species of the genus is given.